[Back to the fold ; Playing with a chance ; Searching for a home [videorecording] /executive producer, Cheche Lazaro. - Lazaro, Cheche (Quezon City Probe Productions, 1993)
An investigative report on the transformation of a respected spokesman for the New People's Army. PAGCOR's putting in more casinoes. Includes interviews with the church, moralists and people on PAGCOR's expanded operations. The opening and closure of Hapag Kalinga Restaurant run by former street children.
Back to the fold (16 min.) -- Playing with a chance (14 min.) -- Searching for a home (10 min.)
VHS.
Keywords: Mabilangan, Leopoldo; New People's Army -- Interviews; Philippine Amusement and Gaming Corporation; Hapag Kalinga Restaurant; Children -- Employment -- Philippines